Substrate recognition by norovirus polymerase: microsecond molecular dynamics study - Maláč, Kamil; Barvík, Ivan (Journal of computer-aided molecular design, 2013)
Molecular dynamics simulations of complexes between Norwalk virus RNA dependent RNA polymerase and its natural CTP and 2dCTP (both containing the O5'-C5'-C4'-O4' sequence of atoms bridging the triphosphate and sugar moiety) or modified coCTP (C5'-O5'-C4'-O4'), cocCTP (C5'-O5'-C4'-C4'') substrates were produced by means of CUDA programmable graphical processing units and the ACEMD software package. It enabled us to gain microsecond MD trajectories clearly showing that similar nucleoside triphosphates can bind surprisingly differently into the active site of the Norwalk virus RNA dependent RNA polymerase. It corresponds to their different modes of action (CTP-substrate, 2dCTP-poor substrate, coCTP-chain terminator, cocCTP-inhibitor). Moreover, extremely rare events-as repetitive pervasion of Arg182 into a potentially reaction promoting arrangement-were captured.
Keywords: RNA-Dependent RNA Polymerase; substrátová specifita; infekce viry z čeledi Caliciviridae; Cytidine Triphosphate; lidé; Humans; simulace molekulární dynamiky; Caliciviridae Infections; simulace molekulového dockingu; Molecular Dynamics Simulation; cytidintrifosfát; Norovirus; Molecular Docking Simulation; Substrate Specificity; RNA-dependentní RNA-polymerasa